2021
DOI: 10.3390/ijms22094515
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of Leaf Senescence in Rice

Abstract: Leaf senescence, which is the last developmental phase of plant growth, is controlled by multiple genetic and environmental factors. Leaf yellowing is a visual indicator of senescence due to the loss of the green pigment chlorophyll. During senescence, the methodical disassembly of macromolecules occurs, facilitating nutrient recycling and translocation from the sink to the source organs, which is critical for plant fitness and productivity. Leaf senescence is a complex and tightly regulated process, with coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 146 publications
2
43
0
2
Order By: Relevance
“…Many studies have demonstrated that hormonal changes at the whole-plant level can regulate senescence and nutrient remobilization (Davies, 1995;Lee and Masclaux-Daubresse, 2021). Abiotic stresses also affect hormonal levels, potentially regulating seed development and nutrient mobility (Ober et al, 1991;Davies, 1995;Wang et al, 2006).…”
Section: Npf and Lt Suppressed Grain Filling Related Characteristicsmentioning
confidence: 99%
“…Many studies have demonstrated that hormonal changes at the whole-plant level can regulate senescence and nutrient remobilization (Davies, 1995;Lee and Masclaux-Daubresse, 2021). Abiotic stresses also affect hormonal levels, potentially regulating seed development and nutrient mobility (Ober et al, 1991;Davies, 1995;Wang et al, 2006).…”
Section: Npf and Lt Suppressed Grain Filling Related Characteristicsmentioning
confidence: 99%
“…Leaf senescence is the last stage of plant growth, and is affected by various genetic and environmental constraints [ 42 ]. Leaf yellowing is a visible symptom of senescence that is caused by loss of the green pigment chlorophyll (Chl) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, many SAGs have been characterized in rice. They are involved in nutrient relocation, macromolecules degradation, transcriptional regulation, and signal transduction (Lee and Masclaux-Daubresse, 2021). Rice plants containing these loss-of-function or gain-of-function SAGs usually exhibit delayed or accelerated leaf senescence.…”
Section: Introductionmentioning
confidence: 99%
“…Rice plants containing these loss-of-function or gain-of-function SAGs usually exhibit delayed or accelerated leaf senescence. Moreover, environmental factors including nutrient status, light quality and length, climate change, water usage, and biotic stress separately or collaboratively modulate leaf senescence (Lee and Masclaux-Daubresse, 2021).…”
Section: Introductionmentioning
confidence: 99%